Peran Layanan Bus Jawara Dalam Meningkatkan Minat Parawisata Di Kota Tangerang - Khaerunnisa, Indah; Syamsudin, Udin; Badar, Refly (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research aims to find out the role of the Jawara Bus service in increasing tourism interest in Tangerang City and to find out the extent of service quality and the role of the Jawara Bus in increasing tourist attraction in Tangerang City. This research uses a descriptive qualitative approach. Data was collected using observation, interviews and documentation techniques. Types and sources of data are primary data and secondary data. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The theoretical concepts used in this research are indicators of the quality of public services that are appropriate and relevant, available and affordable, can guarantee a sense of justice, are acceptable, economical and effective. The problem with this research is that there are still many champion bus users who are wondering about the service system and whether champion buses can only be facilitated by individual communities with certain conditions or can be rented by other civil society groups in Tangerang City. Apart from that, the departure point of the Jawara bus is still not known to many people, so in the end the Jawara bus is only known as a bus that only takes tours and is seen on every trip by the people of Tangerang city. In fact, there are still some people who don't know that there are Jawara buses in Tangerang City. Several other problems that arise are still problems, such as the lack of tourist destinations that the Jawara Bus passes through and the lack of tourists visiting.